2006
DOI: 10.1523/jneurosci.1967-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Pheromone Detection in Male Mice Depends on Signaling through the Type 3 Adenylyl Cyclase in the Main Olfactory Epithelium

Abstract: Terrestrial vertebrates have evolved two anatomically and mechanistically distinct chemosensory structures: the main olfactory epithelium (MOE) and the vomeronasal organ (VNO). Although it has been generally thought that pheromones are detected through the VNO, whereas other chemicals are sensed by the MOE, recent evidence suggests that some pheromones may be detected through the MOE. Odorant receptors in the MOE are coupled to the type 3 adenylyl cyclase (AC3), an enzyme not expressed in the VNO. Consequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
127
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(132 citation statements)
references
References 29 publications
4
127
1
Order By: Relevance
“…olfactory rather than vomeronasal stimuli, with attractive properties for females. Thus, farnesenes and other volatile vomeronasal ligands stimulate the olfactory epithelium (Wang et al, 2006). Lin et al (2005) combined gas chromatography with simultaneous recording of the activity of mitral cells in the main olfactory bulb stimulated by individual volatiles in mouse urine.…”
Section: A Volatile Male Sexual Pheromones: Chemical Species and Thementioning
confidence: 99%
“…olfactory rather than vomeronasal stimuli, with attractive properties for females. Thus, farnesenes and other volatile vomeronasal ligands stimulate the olfactory epithelium (Wang et al, 2006). Lin et al (2005) combined gas chromatography with simultaneous recording of the activity of mitral cells in the main olfactory bulb stimulated by individual volatiles in mouse urine.…”
Section: A Volatile Male Sexual Pheromones: Chemical Species and Thementioning
confidence: 99%
“…In these experiments in which the MOE was ablated, the function of the VNS is not directly disrupted, because the VNS is activated by direct application of urine to the nostril. Thus, these results indicate that the MOS also contributes to pheromone processing and related behaviors.Nonconditional disruption of genes encoding signal transduction proteins that are required for activation of olfactory neurons, such as cyclic nucleotide-gated channel (Cnga2) or adenylyl cyclase 3, impairs several social behaviors (11,(13)(14)(15). However, complete loss of MOS function causes anosmia and severely impairs sniffing and chemoinvestigatory behaviors (11,13,14,16).…”
mentioning
confidence: 99%
“…However, complete loss of MOS function causes anosmia and severely impairs sniffing and chemoinvestigatory behaviors (11,13,14,16). Chemoinvestigation and the accompanying physical contact of the nose and pheromone source are essential for VNS activation; therefore, the loss of MOS function indirectly impairs the VNS, because the VNS becomes behaviorally isolated from pheromone cues in mice (16)(17)(18)(19).…”
mentioning
confidence: 99%
“…Thus, it now is clear that the main olfactory system is involved in detection of semiochemicals and that the cAMP signaling pathway plays an important role in signal transduction for certain pheromones and MHC peptides (16,(19)(20)(21). However, the potential involvement of other signaling pathways is not fully understood (21,22).Previously, we demonstrated that genetic elimination of subunit A2 of the CNG channel, which disrupts the canonical cAMP pathway, significantly reduced but did not eliminate physiological and behavioral responses to pheromones in the main olfactory system (22). The transduction pathway responsible for these responses was not identified, but pharmacological experiments suggested involvement of phospholipase C (PLC).…”
mentioning
confidence: 99%
“…Further, a class of chemosensory receptors that recognize social amines found in urine have been identified recently in the MOE (18). Thus, it now is clear that the main olfactory system is involved in detection of semiochemicals and that the cAMP signaling pathway plays an important role in signal transduction for certain pheromones and MHC peptides (16,(19)(20)(21). However, the potential involvement of other signaling pathways is not fully understood (21,22).…”
mentioning
confidence: 99%